An investigation of the mixed water/formamide solvent on the synthesis of cadmium nitroprusside particles and its behavior in the electrochemical sensing of isoniazid - Souza, Tamires Rocha [UNESP]; Sa, Acelino Cardoso de; Carmo, Devaney Ribeiro do [UNESP] (Springer, 2021)
Size-controlled cadmium nitroprussides, with particles in the micron meter or submicron size range (0.050-1.15 micron), (CdNPs) were prepared from total and varied compositions of water and formamide solvent in the complexation reaction of cadmium and nitroprusside ions. Four analytical systems (CdNP-1, CdNP-2, CdNP-3, and CdNP-4) were set up. The coordinated materials were investigated by spectroscopic and analytical techniques such as Raman spectroscopy, ultraviolet-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), scanning electron microscopy (SEM), and cyclic voltammetry (CV). The CVs of the modified graphite paste electrode with CdNP-1, CdNP-2, CdNP-3, and CdNP-4 (10% m/m) exhibited a defined redox pair with formal potential (E-theta ') = 0.63 +/- 0.02 V (nu = 20 mV s(-1); KNO3 1.0 M). The dependence of particle size on the isoniazid electro-oxidation was verified by CdNP-3 and CdNP-4 microparticles.
Keywords: Cadmium nitroprusside; Spectroscopy; Voltammetry; Isoniazid electro-oxidation; Particle synthesis